Lacanian "Gaze" in John Keats’s "The Eve of St. Agnes": A Romance of Resistance - KEIVAN, Shafigheh (Anafora, 2023)
"The Eve of St. Agnes" is one of Keats’s most challenging poems when it comes to the poet’s emotions and beliefs on social structures, life, death, men, and women. Consequently, The Eve of St. Agnes becomes the arena of the conflict between femininity and masculinity, which preoccupied the poet during the composition of the poem. In the essay, we seek to examine this conflict in The Eve of St. Agnes through the Lacanian concept of the Gaze. This point of view allows us to analyze Keats’s ambivalence towards gender.